2015
DOI: 10.5194/bg-12-595-2015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reed canary grass cultivation on greenhouse gas emission from peat soil at controlled rewetting

Abstract: Abstract. Cultivation of bioenergy crops in rewetted peatland (paludiculture) is considered as a possible land use option to mitigate greenhouse gas (GHG) emissions. However, bioenergy crops like reed canary grass (RCG) can have a complex influence on GHG fluxes. Here we determined the effect of RCG cultivation on GHG emission from peatland rewetted to various extents. Mesocosms were manipulated to three different ground water levels (GWLs), i.e. 0, −10 and −20 cm below the soil surface in a controlled semi-fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
6
7
0
Order By: Relevance
“…Monitoring of environmental variables was achieved by instrumentation of one of five replicate mesocosms at each GWL, assuming that the measured variables were representative for all five mesocosm replicates. Karki et al (2015) previously found that ER, CH 4 and N 2 O fluxes from instrumented and noninstrumented mesocosms (0-20 cm GWL) were similar which substantiated the assumption of similar environmental conditions among the mesocosm replicates.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Monitoring of environmental variables was achieved by instrumentation of one of five replicate mesocosms at each GWL, assuming that the measured variables were representative for all five mesocosm replicates. Karki et al (2015) previously found that ER, CH 4 and N 2 O fluxes from instrumented and noninstrumented mesocosms (0-20 cm GWL) were similar which substantiated the assumption of similar environmental conditions among the mesocosm replicates.…”
Section: Discussionsupporting
confidence: 54%
“…Karki et al . () previously found that ER, CH 4 and N 2 O fluxes from instrumented and noninstrumented mesocosms (0–20 cm GWL) were similar which substantiated the assumption of similar environmental conditions among the mesocosm replicates.…”
Section: Discussionmentioning
confidence: 97%
“…Our simulated RCG growth, 11.7 (11.3–12.7) Mg CO 2 ha −1 year −1 , also falls within reported yields of 9–16 Mg CO 2 ha −1 year −1 for southern Sweden and Denmark, respectively (Karki et al., ; Landström, Lomakka, & Andersson, ). Interestingly, all three drained scenarios showed rather similar biomass growth rates despite different WTD settings (Figure ), which only slightly increased with lower WTD, also reported in a study by (Karki, Elsgaard, & Laerke, ). However, in their study, the WTD varied only between 0 and −20 cm.…”
Section: Discussionsupporting
confidence: 85%
“…However, the simulation showed this respiration to be sensitive to WTD and plant systems, as Scenarios 2, 3, and 4 had heterotrophic respirations (peat and litter respiration) of 14, 9, and 3 Mg CO 2 ha −1 year −1 , respectively. This is similar to heterotrophic respiration for fen rewetting and RCG cropping in Denmark at a WTD of 0 to −20 cm, and 10–20 Mg CO 2 eq ha −1 year −1 (Karki et al., ). This notwithstanding, higher respiration was found in a mesocosm study with RCG, where dark respiration measured by chambers was 40–70 Mg CO 2 ha −1 year −1 for WTD of 0–20 cm (Karki, Elsgaard, Kandel, & Laerke, ).…”
Section: Discussionsupporting
confidence: 70%
“…In contrast to previous studies suggesting that RCG cultivations provide negative GHG balances and thus mitigate the GHG emissions from drained organic soils (Shurpali et al, 2010;Mander et al, 2012), both the fertilized and nonfertilized RCG systems had positive GHG balances in the current study due to the exceptionally dry conditions during the studied year. However, previous studies indicate that a negative GHG balance could be achieved by cultivating RCG in agricultural systems with elevated WTL and sufficient soil water availability (K€ atterer & Andr en, 1999;Freibauer et al, 2004;Schrier-Uijl et al, 2014;Karki et al, 2015b). Although raising the WTL in drained organic soils might result in increased CH 4 emissions, these increases have been estimated to be modest (Komulainen et al, 1998;Tuittila et al, 2000;Wilson et al, 2009;Karki et al, 2014), and are therefore unlikely to compromise the benefits gained from increased plant growth and CO 2 uptake due to sufficient water supply.…”
Section: The Full Carbon Balancementioning
confidence: 99%